Study on a new method of controlling casing shear deformation based on hollow glass microspheres cement sheath. (November 2022) - Liu, Penglin; Li, Jun; Yang, Hongwei; Zhang, Hui; Lian, Wei; Gao, Reyu; Zhang, Xiaojun
Abstract: Casing shear deformation caused by fault slip is a serious problem that restricts shale gas development. As yet, there is no effective method for controlling casing shear deformation. In this study, a cement sheath with hollow glass microspheres was used to prevent and mitigate casing deformation caused by a fault slip. An equivalent outer-diameter model was established. This model analyzes the mechanism by which casing shear deformation is controlled by a cement sheath with hollow glass microspheres under the condition of fault slip. The hollow glass microspheres in the cement sheath were broken owing to the strong shear forces of the fault slip. The internal volume of the hollow glass microspheres was released, which reduced the distance of the fault slip across the casing. The casing deformation was prevented or slowed down. A 3D assembly numerical model was established to evaluate the control effect of the hollow glass microspheres on casing shear deformation. Furthermore, the influences of slip distance, casing thickness, mechanical parameters of formation, mechanical parameters of the cement sheath, and crustal stress difference were analyzed. The mathematical calculation results showed that casing deformation increased with an increase in the fault slip distance, an increase in the stratum elastic modulus, and a decrease in the in situ stress difference. Therefore, the mass content of the hollow glass microspheres in the cement sheath also needs to be increased to ensure that the casing does not deform. The numerical analysis results showed that the change in casing thickness, Poisson's ratio of formation, and mechanical parameters of the cement sheath had little effect on the mass content of hollow glass microspheres. Finally, the model was used to analyze the test wells in the Weirong Block, Sichuan, China. The calculation results showed that under the same condition of casing deformation of 8.23 mm in adjacent wells, casing shear deformation could be avoided by using a cement sheath with 11.9% hollow glass microspheres in the test well. This study provides a theoretical basis and reference for controlling the casing shear deformation caused by fault slip in shale gas wells. Highlights: A method of controlling casing shear deformation by hollow glass microspheres (HGM) was proposed. A numerical model was established to analyze the influence of different HGM contents on casing shear deformation. The lower the HGM density and the higher the HGM content, the better the cement sheath with HGM could control the casing deformation.